Inosine 5′-diphosphate, a molecular decoy rescues Nucleoside diphosphate kinase from c-MYC G-Quadruplex unfolding - Sengupta, Pallabi; Chatterjee, Subhrangsu (Biochimica et biophysica acta. General subjects, 2020)
The transcription-inhibitory G-Quadruplex(Pu27-GQ) at c-MYC promoter is challenging to target due to structural heterogeneity. Nucleoside diphosphate kinase (NM23-H2) specifically binds and unfolds Pu27-GQ to increase c-MYC transcription. Here, we used Inosine 5′-diphosphate (IDP) to disrupt NM23-H2-Pu27-GQ interactions and arrest c-MYC transcription without compromising NM23-H2-mediated kinase properties. Site-directed mutagenesis,31P‐NMR and STD-NMR studies delineate the epitope of NM23-H2-IDP complex and characterize specific amino acids in NM23-H2 involved in Pu27-GQ and IDP interactions. Immunoprecipitations and phosphohistidine-immunoblots reveal how IDP blocks NM23-H2-Pu27 association to downregulate c-MYC transcription in MDAMB-231 cells exempting NM23-H2-mediated kinase properties. NMR studies show that IDP binds to the Guanosine diphosphate-binding pocket of NM23-H2 (KD = 5.0 ± 0.276 μM). Arg88-driven hydrogen bonds to the terminal phosphate of IDP restricts P–O–P bond-rotation increasing its pKa (∆pKa = 0.85 ± 0.0025).9-inosinyl moiety of IDP is stacked over Phe60 phenyl ring driving trans-conformation of inosine and axial geometry of pyrophosphates. Chromatin immunoprecipitations revealed that these interactions rescue NM23-H2-driven Pu27-GQ unfolding, which triggers Nucleolin recruitment and lowers Sp1 occupancy at c-MYC promoter stabilizing Pu27-GQ. This silences c-MYC transcription that reduces c-MYC-Sp1 association amplifying Sp1 recruitment across P21 promoter stimulating P21 transcription and G2/M arrest. IDP synergizes the effects of Pu27-GQ-interacting compounds to abrogate c-MYC transcription and induce apoptosis in MDAMB-231 cells by disrupting NM23-H2-Pu27-GQ interactions without affecting NM23-H2-mediated kinase properties. Our study provides a pragmatic approach for developing NM23-H2-targeting regulators to rescue NM23-H2 binding at structurally ambiguous Pu27-GQ that synergizes the anti-tumorigenic effects of GQ-based therapeutics with minimized off-target effects. •IDP, a decoy substrate of NM23-H2 binds to its GDP-binding pocket.•IDP disrupts the interactions between NM23-H2 and c-MYC G-Quadruplex (Pu27-GQ).•F60 and R88 of NM23-H2 are involved in both IDP and Pu27-GQ binding.•IDP induces Nucleolin occupancy to Pu27-GQ offering higher G-Quadruplex stability.•IDP synergizes c-MYC transcription-silencing effects of Pu27-GQ-binding ligands.